1992
DOI: 10.1111/j.1460-9568.1992.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nitric Oxide in Long‐term Potentiation

Abstract: Nitric oxide production in the cerebellum and induction of long-term potentiation (LTP) in the hippocampus have some characteristics in common: both phenomena are induced by activation of N-methyl-d-aspartate receptors and both are highly dependent on calcium-mediated processes. Here we provide evidence that endogenous nitric oxide production is necessary for synaptic plasticity in the CA1 hippocampus of the rat. LTP recorded in slices was blocked in a concentration-dependent manner by the nitric oxide synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(58 citation statements)
references
References 41 publications
2
54
1
1
Order By: Relevance
“…NO, in its turn, enhances vesicular release by stimulating cGMP synthesis at the presynaptic site and upregulates trafficking of AMPA receptors at the postsynaptic site [67]. Thereby, it may contribute to the induction of ATPinduced LTP like it has been demonstrated for tetanusinduced LTP [68][69][70][71][72]. The present study indicates that longterm synaptic plasticity induced by ATP is cannabinoiddependent: ATP-induced LTP is inhibited by the activation CB1 receptors.…”
Section: Discussionsupporting
confidence: 72%
“…NO, in its turn, enhances vesicular release by stimulating cGMP synthesis at the presynaptic site and upregulates trafficking of AMPA receptors at the postsynaptic site [67]. Thereby, it may contribute to the induction of ATPinduced LTP like it has been demonstrated for tetanusinduced LTP [68][69][70][71][72]. The present study indicates that longterm synaptic plasticity induced by ATP is cannabinoiddependent: ATP-induced LTP is inhibited by the activation CB1 receptors.…”
Section: Discussionsupporting
confidence: 72%
“…In these cells NO has been implicated in synaptic plasticity phenomena like long-term potentiation (LTP) in the hippocampus [1,2] and long-term synaptic depression (LTD) in the cerebellum [21]. In these processes NO is suggested to act as a possible retrograde messenger, carrying information from postsynaptic elements (e.g., CAI pyramidal neurons and cerebellar Purkinje cells) to presynaptic terminals [see ref .…”
Section: Discussionmentioning
confidence: 99%
“…However, a few groups have had some www.annualreviews.org/aronline Annual Reviews success. Bohme and colleagues (Bohme et al 1991, Bon et al 1992 have shown that extracellular application of two different NO donors, hydroxylamine and sodium nitroprusside, can potentiate synaptic transmission in a manner that occludes normal synaptically-induced LTP. Direct application of NO has also been demonstrated to augment synaptic transmission: in cultured hippocampal neurons NO increases the frequency of spontaneous miniature synaptic events (O'Dell et al 1991).…”
Section: Long-term Potentiationmentioning
confidence: 99%